INTERNATIONAL MARKET ORIENTATION FOCUSING FACTORS, THEIR POWER AND SIGNIFICANCE - Vedran Stanetić (Zbornik Radova Ekonomskog Fakulteta u Istočnom Sarajevu, 2011)
A new approach to solvingeconomic problems in the Republic of Srpska, inrelation to current practice, should includesignificant changes in the way of doing business byenterprises and entrepreneurs. International marketorientation should be the basis of that change, andeconomic problems of the Republic of Srpska canbe solved only with adequate involvement in theinternational flows of goods, services andinformation. For a long time small, medium andlarge companies from all over the world have beentrying to find a chance for their development andsurvival on the international market. Companiesthat stand outside the world or regional tradeflows, at best, remain languishing on the domesticmarket without any great opportunities for progressand development. There are many reasons for noninvolvement in the regional and world trade flows.The most important reason of that is laziness of theenterprises, and fear of failure. The first can beignored because it is not within the domain of thispaper. Attention is paid to another problem, or howto overcome the perception of the internationalmarket as something unknown.